The line of dignity as an indicator of social and environmental sustainability: progress from the concept of minimum life to the concept of decent life (Polis (Santiago), 2018)
The author presents the concept of "Dignity Line" as the framework that focuses discussions on social and environmental sustainability between civil society of the North and South, seeking to reconcile the objectives of environmental sustainability with the distributional goals of social equity and participatory democracy. The author traces the history of the concept and then follows the conceptual work of the Southern Cone Program, eventually postulating the need for the ethical dimension that demands building North-South sustainability.
Keywords: line of dignity; sustainability; civil society; Southern Cone